Family health behaviors - Itzik Fadlon; Torben Heien Nielsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2017)
This paper studies how health behaviors and investments are shaped through intra- and inter-generational family spillovers. Specffically, leveraging administrative healthcare data, we identify the effects of health shocks to individuals on their family members' consumption of preventive care and utilization indicative of health-related behaviors. Our identification strategy relies on the timing of shocks by constructing counterfactuals to affected households using households that experience the same shock but a few years in the future. We find that spouses and adult children immediately increase their health investments and improve their health behaviors in response to family shocks, and that these effects are both significant and persistent for at least several years. Notably, we find that these spillover effects in consumption of healthcare are far-reaching and cascade to siblings, stepchildren, sons and daughters in-law, and even "close" coworkers. Using different strategies we show that while a variety of mechanisms seem to be at play, including learning new information about one's own health, there is consistent evidence in support of salience as a major operative explanation, even when the family shock was likely uninformative. Our results have implications for models of health behaviors, by underscoring the importance of one's family and social network in their determination, and are potentially informative for policies that aim to improve population health.
Keywords: 330; Gesundheitsvorsorge; Familie; Intergenerationale Übertragung; Spillover-Effekt